2017
DOI: 10.1186/s12891-017-1904-7
|View full text |Cite
|
Sign up to set email alerts
|

How to avoid unintended valgus alignment in distal femoral derotational osteotomy for treatment of femoral torsional malalignment - a concept study

Abstract: BackgroundDefining the optimal cutting plane for derotational osteotomy at the distal femur for correction of torsion in cases of patellofemoral instability is still challenging. This preliminary study investigates changes of frontal alignment by a simplified trigonometrical model and demonstrates a surgical guidance technique with the use of femur cadavers. The hypothesis was that regardless of midshaft bowing, a cutting plane perpendicular to the virtual anatomic shaft axis avoids unintended valgus malalignm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 26 publications
0
7
0
1
Order By: Relevance
“…Trigonometric calculations showed varus producing effects after a simple internal rotation of the proximal limb when the cutting plane was 90 degrees to the proximal virtual anatomical axis (regarding the greater trochanter) [ 22 ]. Table 2 shows the change of AMA at a defined torsion angle, which is independent from limb length, (formula is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Trigonometric calculations showed varus producing effects after a simple internal rotation of the proximal limb when the cutting plane was 90 degrees to the proximal virtual anatomical axis (regarding the greater trochanter) [ 22 ]. Table 2 shows the change of AMA at a defined torsion angle, which is independent from limb length, (formula is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The guide was aligned parallel to the virtual anatomic axis from a coronal view and parallel to the virtual anatomical axis from a sagittal view. The virtual anatomical axis is a line from the middle of the proximal shaft at the greater trochanter to the middle of the distal shaft at the assumed height of the cutting plane, on a frontal and a sagittal view [ 22 ]. For rotational control, two 2.5 mm k-wires were inserted from anterior to posterior, one proximal to the assumed osteotomy and one on the distal side.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nelitz et al [26] have proposed that if the coronal plane is in varus, the osteotomy must be performed in the distal metaphysis, and like in this case study, if the coronal alignment is neutral, a transverse osteotomy on the shaft of the femur must be done. However, Imhoff et al demonstrated, in a cadaveric study, the importance of the orientation of the cut in the distal femur to avoid changes in the coronal orientation of the limb, when a distal femoral derotational osteotomy is performed [27]. More importantly, by a single cut in the distal femur, the coronal and the rotational problem of the patient can be addressed by choosing the patient-specific oblique cut [28]; these promising results must be validated in the operating room.…”
Section: Discussionmentioning
confidence: 99%
“…However, other authors propose to perform the osteotomy perpendicular to the femoral mechanical axis [13], possibly with less influence on the postoperative mechanical leg axis. There are different other attempts for preoperative planning of the correct osteotomy plane in femoral rotational osteotomies [14][15][16]. Nonetheless, implementation of the preoperative planning into the surgical situation can be challenging, wherefore some deviation from the planning is likely in most cases.…”
Section: Introductionmentioning
confidence: 99%